Peningkatan Kesadaran Kesehatan melalui Deteksi Dini Hipertensi dan Penyuluhan Kesehatan - Agnes Fibriana Kurniawati; Veroneka Yosefpa Windahandayani; Bangun Dwi Hardika (Pusat Riset dan Inovasi Nasional, 2024)
Hypertension can lead to serious complications such as heart disease, stroke, and kidney damage. The prevalence of hypertension often goes undetected due to minimal symptoms, so many individuals are unaware of it. Early detection through routine blood pressure measurements and health education is important for risk identification and effective management of hypertension. Blood pressure checks and health education are important first steps in raising public health awareness. This activity aims to identify individual health conditions and provide the knowledge necessary to maintain optimal health. From the data obtained, 14% of participants showed symptoms of hypotension, 66% had normal blood pressure, and 20% already had hypertension. These results show the need for continuous efforts in blood pressure monitoring and health education to reduce the risk of blood pressure-related diseases. This service emphasizes the importance of early detection and increased public understanding of the importance of keeping blood pressure within the normal range to prevent further health complications.